Incidence of brain parenchymal abnormality in a group of HIV positive patients admitted in tertiary care hospital: a prospective descriptive study - Nath, S. K.; Sudumbrekar, S. M.; Arora, Sumeet; Rai, S. K. (International Surgery Journal, 2018)
Background: Magnetic resonance imaging (MRI) has been used to examine the impact of human immunodeficiency virus (HIV) on the central nervous system (CNS) since the beginning of the disease. The objectives of this study were to determine the incidence of brain parenchymal abnormality in a group of HIV positive patients and to detect and study the profile of MRI patterns of brain lesions in HIV positive patients. Methods: In our study, total of 28 patients have been evaluated enrolled between 01 December 2013 to 30 December 2014. Results: During the study period 35 patients on immune-surveillance were screened for brain lesions of which 28 patients met the inclusion criteria and were included in study. The male-female ratio has been found to be 4.6:1 with the mean age of 43 (18-77). Majority of patients presented with headache as main clinical symptom. Out of which 20% normal, 13.3% NSWM, 13.3% atrophy, hematoma 6.6%, infarct 6.6%, toxoplasmosis 13.3%, PML 13.3%, NCC 6.6% and CMV encephalitis 6.6%. Altered mental status and neurological deficit 27.6% and 20.7%, respectively, were two other symptoms following headache. MR imaging detected neuroparenchymal abnormality in 20 (71.4%), out of 28 HIV positive patients. There was no neuroparenchymal abnormality seen in the rest of the 08 patients Conclusions: MR imaging detected neuroparenchymal abnormality in 20 (71.4%), out of 28 HIV positive patients. Based on our study we can conclude that the MRI of brain is the primary modality to detect the brain lesion in HIV positive patient even if he is asymptomatic clinically.